Financialisation, sustainable finance and innovative financing for development mechanisms: the greek case study for crowdfunding and green bonds - Boufounou, Paraskevi; Dellis, Konstantinos (International Conference on Business and Economics - Hellenic Open University, 2023)
In this study we look at the potential of these novel financial instruments namely the Innovative Financing for Development Mechanisms (IFDMs). Bearing in mind the adverse financial conditions in many emerging and advanced economies, the high risk associated to innovative activities and intangible assets, the growing levels of private and public debt and the need to address sustainability on top of economic growth, these instruments are of pivotal importance. We consider the Greek economy as a case study and elaborating on the structure and functioning of crowdfunding and green bonds, we identify the potential given the current financial adversities, but also highlight the need for a comprehensive global governance and legislation built around those tools, concluding that these innovative forms of finance although currently at a premature level compared to regional averages, could play a considerable part in the rejuvenation of the domestic financial system in this time of need EL Classifications: G20, G21, G23, O10, O16. Key words: Financialization, Sustainable Development, Crowdfunding, Green Bonds This work was financially supported by the Department of Economics, National and Kapodistrian University of Athens